Spatial variation of dose rate from beta sources as measured using single grains - Ballarini, M.; Wintle, A. G.; Wallinga, J. (Ancient TL, 2006)
Dose rates across the centre of a 9.7 mm diameter aluminium disc were measured using a 10 x 10 array of single grains of quartz held in holes drilled with 600 μm separation. The dose rates were obtained by measuring the OSL signals from quartz grains that previously had been given a known gamma dose and comparing them with those measured following increasing doses given by a beta source held 5 mm above the disc surface. The patterns of dose rate were obtained for four 90Sr/90Y beta sources. Two were found to produce a non-uniform dose rate at the disc surface, with one showing a factor of two across the 7.6 mm diameter of the area containing the 10 x 10 array. The implications for both single grain and multiple grain measurements are discussed.